2006
DOI: 10.1039/b602435a
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron imaging following 2 + 1 multiphoton excitation of HBr

Abstract: The photodissociation and photoionization dynamics of HBr via low-n Rydberg and ion-pair states was studied by using 2 + 1 REMPI spectroscopy and velocity map imaging of photoelectrons. Two-photon excitation at about 9.4-10 eV was used to prepare rotationally selected excited states. Following absorption of the third photon the unperturbed F (1)Delta(2) and i (3)Delta(2) states ionize directly into the ground vibrational state of the molecular ion according to the Franck-Condon principle and upon preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…The focus of the work summarized here lies in the investigation of the photoionization of HCl following two-photon excitation of its Rydberg states. For HBr [1][2][3], and to a lesser extent for HI [4], similar studies and similar conclusions have been reported, whereas much less is known about HF, most probably due to the difficulty of state-selective fluorine atom detection [5] and to the more problematic chemical properties of HF making gas handling significantly more demanding.…”
Section: Introductionsupporting
confidence: 53%
“…The focus of the work summarized here lies in the investigation of the photoionization of HCl following two-photon excitation of its Rydberg states. For HBr [1][2][3], and to a lesser extent for HI [4], similar studies and similar conclusions have been reported, whereas much less is known about HF, most probably due to the difficulty of state-selective fluorine atom detection [5] and to the more problematic chemical properties of HF making gas handling significantly more demanding.…”
Section: Introductionsupporting
confidence: 53%
“…14 The larger spin-orbit interaction in HBr compared to HCl results in a departure from a Hund's case ͑a͒ description with the result that, for the perpendicular two-photon pathway, both the 1 ⌸ 1 and 3 ⌸ 1 states are able to contribute. [43][44][45] More importantly, for the parallel pathway, the 3 ⌸ 0 (⍀ϭ0) intermediate state gains strength through spin-orbit mixing with the ground state.…”
Section: Photodissociation Of Hbrmentioning
confidence: 99%
“…The effects of this prepared angular momentum polarization upon the observed vector correlations are pronounced and complicated. [12][13][14] Control over the prepared angular momentum polarization provides a powerful tool for the interrogation of the photodissociation dynamics, allowing for control over which electronic states are active in the photodissociation. 12,15 In essence, a state of known angular momentum polarization ͑and molecular axis alignment/orientation͒ allows for control over the molecular frame geometry in the laboratory frame and so control over the molecular frame transition dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…1-13͒ and HBr, [14][15][16][17][18][19] are perhaps the most studied diatomic molecules in the field of photodissociation and photoionization dynamics. 1-13͒ and HBr, [14][15][16][17][18][19] are perhaps the most studied diatomic molecules in the field of photodissociation and photoionization dynamics.…”
Section: Introductionmentioning
confidence: 99%